2018
DOI: 10.1039/c8ra07638c
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic molecule (O2, NO) adsorption on nitrogen- and phosphorus-doped MoS2 monolayer using first principle calculations

Abstract: We performed a systematic study of the adsorption behaviors of O2 and NO gas molecules on pristine MoS2, N-doped, and P-doped MoS2 monolayers via first principle calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…et al modified MoS 2 with non-metallic atoms N and P, and tested the adsorption of O 2 and NO. They found that the adsorption effects of modified N-MoS 2 and P-MoS 2 were stronger than that of intrinsic MoS 2 [ 19 ]. Ga is a common semiconductor dopant, which is used as the dopant of nitrogen, arsenic, phosphorus, and other elements.…”
Section: Introductionmentioning
confidence: 99%
“…et al modified MoS 2 with non-metallic atoms N and P, and tested the adsorption of O 2 and NO. They found that the adsorption effects of modified N-MoS 2 and P-MoS 2 were stronger than that of intrinsic MoS 2 [ 19 ]. Ga is a common semiconductor dopant, which is used as the dopant of nitrogen, arsenic, phosphorus, and other elements.…”
Section: Introductionmentioning
confidence: 99%
“…Mouri et al achieves the tunable photoluminescence (PL) of 1L MoS 2 by adding some organic impurities . Furthermore, some researchers predict the possible doping paradigms of MoS 2 and study the properties of these extrinsic MoS 2 theoretically. Doping engineering could extremely extend the application fields of 2D MoS 2 via renormalizing electronic structures, adjusting conduction types, and optimizing physicochemical properties . Compared with the nonintrinsic 2D MoS 2 obtained by electrostatic doping and contact engineering, 2D-doped MoS 2 directly synthesized by chemical doping processes should have excellent thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Ni-MoS 2 shows strong adsorption to O 2 [24][25][26][27][28][29][30][31][32][33]. Ni-doped MoS 2 film sensors have been verified to be a suitable candidate to detect SO 2 , one typical decomposition product of SF 6 [34]. Some experimental results have shown that the Pt-TiO 2 /MoS 2 film sensor has a high gas-sensing response and excellent repeatability [35].…”
Section: Introductionmentioning
confidence: 99%